A negative electrode active material, a method for preparing the same, and an application thereof

CN122930863APending Publication Date: 2026-10-16HEFEI GUOXUAN HIGH TECH POWER ENERGY +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610898190.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-18
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

然而,在全固态锂离子电池体系中,硅负极面临本征电子电导率和离子迁移率较低、充放电过程中体积膨胀超过300%导致颗粒破碎和界面脱粘,以及与硫化物固态电解质发生不可逆分解反应等问题,导致界面阻抗快速增加和容量衰减严重

Benefits of technology

本发明提供的负极活性材料含有无定形复合层,其具有较高的锂离子电导率和连续性,可在硅负极表面构筑快速、稳定的离子传输通道,降低界面极化;同时无定形复合层具有一定弹性模量和良好机械柔顺性,可在充放电过程中吸收和分散硅颗粒体积膨胀产生的应力,避免颗粒粉化和界面脱粘,有效抑制界面副反应,降低界面阻抗,提升电池的循环稳定性和倍率性能;本发明提供的工艺制备过程简单、条件温和、易于放大,适合产业化制备。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122930863A_ABST
    Figure CN122930863A_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of solid-state batteries, and relates to a negative electrode active material and a preparation method and application thereof. The negative electrode active material comprises a silicon-based inner core and an amorphous composite layer in-situ coated on the surface of the silicon-based inner core. In the XRD pattern of the negative electrode active material, only characteristic diffraction peaks of elemental silicon appear, and no crystal state characteristic peaks of raw materials corresponding to the amorphous composite layer appear. The amorphous composite layer has high lithium ion conductivity and good mechanical compliance, can significantly improve the ion transmission performance between the surface of the silicon negative electrode and the sulfide solid-state electrolyte, buffer the volume expansion of silicon in the charging and discharging process, inhibit particle pulverization and interface failure. Meanwhile, the amorphous composite layer can effectively inhibit the interface side reaction and improve the interface chemical stability. The full solid-state lithium ion battery assembled by using the negative electrode active material has high initial coulomb efficiency, low interface impedance and excellent cycle performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of solid-state battery materials technology. Specifically, it relates to a negative electrode active material, its preparation method, and its application. Background Technology

[0002] With the rapid development of new energy vehicles, large-scale energy storage, and portable electronic devices, lithium-ion batteries are evolving towards higher energy density, higher safety, and longer cycle life. All-solid-state lithium batteries, which use solid-state electrolytes to replace flammable liquid electrolytes, are considered an important direction for the development of next-generation batteries. Among them, sulfide solid electrolytes have become a key focus of current research and industrialization due to their high ionic conductivity at room temperature and good compaction properties.

[0003] The silicon anode has a capacity of approximately 4200 mAh g. -1 Silicon anodes are considered ideal anode active materials to replace graphite and significantly improve battery energy density due to their high theoretical specific capacity, moderate lithium intercalation potential, and abundant resources. However, in all-solid-state lithium-ion battery systems, silicon anodes face problems such as low intrinsic electronic conductivity and ion mobility, volume expansion exceeding 300% during charge and discharge leading to particle breakage and interface debonding, and irreversible decomposition reactions with sulfide solid electrolytes, resulting in rapid increases in interface impedance and severe capacity decay.

[0004] In existing technologies, ion transport channels can be introduced into the electrode interior through simple mechanical mixing of sulfide solid electrolytes and silicon powder. However, this often requires adding a high proportion of sulfide solid electrolytes, diluting the active material content and failing to fundamentally solve the problems of interfacial chemical stability and volume expansion. On the other hand, while coating silicon particles with oxides, fluorides, or polymers can improve interfacial contact to some extent, traditional coatings have limited ionic conductivity, insufficient mechanical flexibility, complex preparation processes, and unsatisfactory chemical compatibility with sulfide solid electrolytes. Therefore, there is an urgent need to develop a silicon-based composite anode active material that combines high ionic conductivity, good mechanical buffering performance, and interfacial chemical stability. Summary of the Invention

[0005] In view of the above-mentioned problems in the prior art, the present invention provides a negative electrode active material, characterized in that it comprises: a silicon-based core, and an amorphous composite layer in situ coated on the surface of the silicon-based core; In the XRD pattern of the negative electrode active material, only the characteristic diffraction peaks of elemental silicon appear, and the crystalline characteristic peaks of the raw material corresponding to the amorphous composite layer do not appear.

[0006] In some embodiments, the average particle size D50 of the silicon-based core is 50 nm to 5 μm; in some embodiments, the average particle size D50 of the silicon-based core is 50 nm to 500 nm.

[0007] In some embodiments, the amorphous composite layer has a mass fraction of 2wt% to 30wt% in the negative electrode active material; in some embodiments, the amorphous composite layer has a mass fraction of 5wt% to 20wt% in the negative electrode active material.

[0008] In some embodiments, the amorphous composite layer is generated by an in-situ reaction of lithium fluoride, zirconium fluoride, and the silicon-based core.

[0009] In some embodiments, the amorphous composite layer contains Li, Zr and F elements, and the molar ratio of Li, Zr and F satisfies: Li:Zr:F = (0.5~3) : (0.2~1) : (3~8); in some embodiments, the molar ratio of Li, Zr and F in the amorphous composite layer satisfies: Li:Zr:F = 2:1:6.

[0010] In this invention, lithium fluoride (LiF) and zirconium fluoride (ZrF4) in a molar ratio of 1:(0.2~1.5) can significantly reduce the eutectic point, which is much lower than the melting point of a single component, thus achieving a molten state at a relatively mild temperature. During the melting stage, lithium fluoride and zirconium fluoride first undergo the following eutectic reaction to generate a low-eutectic-point Li-Zr-F ternary molten salt phase: xLiF + yZrF4 → Li x Zr y F (x+4y) .

[0011] Li-Zr-F ternary molten salt can spread on the surface of silicon particles, where F in the molten salt - It can undergo substitution reactions with hydroxyl groups or metastable oxide layers on the silicon surface to generate Si–F bonds and break the original Si–O bonds, thereby achieving in-situ chemical bonding between Li–Zr–F molten salt and the silicon surface. This can be represented by the following chemical formula: Si–OH + F - → Si–F + OH - , Si–O–Si + 2F - → 2Si–F + O 2- , The above reaction achieves in-situ chemical bonding between Li–Zr–F molten salt and silicon surface, rather than simply physical adsorption.

[0012] In some embodiments, the characteristic diffraction peaks of the elemental silicon are located at 2θ of 28°±0.5°, 47°±0.5°, and 56°±0.5°.

[0013] This invention provides a method for preparing the aforementioned negative electrode active material, comprising the following steps: S1. Nano-silicon powder, lithium fluoride and zirconium fluoride are mixed to obtain a premixed powder; S2. The premixed powder is heat-treated to cause lithium fluoride and zirconium fluoride to react in situ on the surface of nano-silicon powder to generate the amorphous composite layer.

[0014] In some embodiments, the mixing process includes a mechanical grinding process, wherein the mechanical grinding process is selected from at least one of ball milling, sand milling, planetary milling, and roller milling; in some embodiments, the mixing process is ball milling.

[0015] In some embodiments, the present invention employs a novel process route of ball milling premixing followed by in-situ reaction. First, silicon powder particles are ball-milled and mixed with lithium fluoride and zirconium fluoride powders to uniformly disperse the two fluorides and initially adhere them to the surface of the silicon particles. Subsequently, the temperature is raised to form a low eutectic point molten salt (the eutectic point is much lower than that of the single component). The molten Li-Zr-F has extremely low viscosity and extremely strong wetting ability, which can quickly spread on the surface of silicon particles and undergo in-situ chemical bonding reaction.

[0016] In some embodiments, the ball-to-particle ratio of the mixed treatment is (15~25):1.

[0017] In some embodiments, the mixing speed is 50-500 rpm; in other embodiments, the mixing speed is 100-300 rpm.

[0018] In some embodiments, the mixing process takes 0.5 to 6 hours; in some embodiments, the mixing process takes 1 to 5 hours; and in some embodiments, the mixing process takes 2 to 4 hours.

[0019] In some embodiments, the heat treatment is performed under an inert atmosphere; in some embodiments, the inert atmosphere is selected from at least one of helium, neon, argon, and nitrogen; in some embodiments, the inert atmosphere is argon.

[0020] In some embodiments, the heat treatment temperature is 400°C to 900°C, and in some embodiments, the heat treatment temperature is 450°C to 550°C.

[0021] In some embodiments, the heat treatment holding time is 0.5 to 4 hours; in other embodiments, the heat treatment holding time is 1 to 3 hours.

[0022] In some embodiments, after the heat treatment, the process further includes: rapidly cooling, grinding, and sieving the heat-treated product; wherein the rapid cooling condition is: reducing the product temperature to room temperature within 5-10 minutes.

[0023] In some embodiments, the sieve mesh size is 400 mesh or larger.

[0024] During the rapid cooling process in this invention, the Li-Zr-F ternary molten salt is difficult to recrystallize, ultimately solidifying on the surface of silicon particles into an amorphous Li–Zr–F fluorine-containing fast ion conductor layer. This amorphous phase fluorine-containing fast ion conductor layer exhibits high ionic conductivity. After being tightly composited with the silicon anode active material, it provides a channel for rapid lithium-ion transport, significantly improving the lithium-ion conductivity of the silicon-based composite material. Simultaneously, in terms of mechanical properties, the amorphous Li-Zr-F phase can limit the volume expansion of the silicon anode during the lithiation process, preventing silicon particle pulverization, while maintaining close physical contact with the sulfide solid electrolyte, preventing interface debonding and ion channel interruption.

[0025] In one aspect, this invention provides an application of the aforementioned negative electrode active material in an all-solid-state battery.

[0026] The present invention provides a secondary battery, characterized in that it includes the aforementioned negative electrode active material.

[0027] In some embodiments, the secondary battery is a lithium-ion battery; in some embodiments, the lithium-ion battery is an all-solid-state lithium-ion battery; in some embodiments, the sulfide solid electrolyte of the all-solid-state lithium battery is Li2S–P2S5 or Li7P3S. 11 Li6PS5Cl, Li 5.5 PS 4.5 Cl 1.5 Li6PS5Br, Li6PS5I, Li 11 Si2PS 12 One or more of them.

[0028] The present invention has the following beneficial effects: The negative electrode active material provided by this invention contains an amorphous composite layer, which has high lithium-ion conductivity and continuity, enabling the construction of fast and stable ion transport channels on the silicon negative electrode surface and reducing interfacial polarization. Simultaneously, the amorphous composite layer possesses a certain elastic modulus and good mechanical flexibility, absorbing and dispersing the stress generated by the volume expansion of silicon particles during charging and discharging, preventing particle pulverization and interfacial debonding, effectively suppressing interfacial side reactions, reducing interfacial impedance, and improving the cycle stability and rate performance of the battery. The process provided by this invention is simple, has mild conditions, is easy to scale up, and is suitable for industrial-scale production. Attached Figure Description

[0029] Figure 1 The following are powder X-ray diffraction (XRD) patterns of the negative electrode active materials prepared in Examples 1-4 and Comparative Example 1 of this invention. In the figure, ZrF4PDF#97-003-5100, LiFPDF#97-004-4272, and SiPDF#27-1402 are the PDF standard cards corresponding to each substance. Figure 2 The images show scanning electron microscope (SEM) images and elemental distribution of the negative electrode active material prepared in Example 1 of this invention, including: (a) SEM image of Si@Li-Zr-F-5% at 10K magnification; (b) SEM image of Si@Li-Zr-F-5% at 30K magnification; (c) SEM image of Si@Li-Zr-F-5% at 30K magnification; and (df) elemental distribution of Si@Li-Zr-F-5% in the material. Figure 3 Scanning electron microscope images and elemental distribution of the negative electrode active materials prepared in Comparative Examples 1(a) and 2(b) of this invention; Figure 4 The cycling performance diagrams are for all-solid-state half-cells assembled from the negative electrode active materials prepared in Examples 1-4 and Comparative Example 1 of this invention. Figure 5 The AC impedance diagrams are of all-solid-state half-cells assembled from the negative electrode active materials prepared in Example 1 and Comparative Examples 1-2 of this invention. Figure 6 The graph shows the cycle performance of an all-solid-state battery assembled from the negative electrode active material (Si@Li-Zr-F-5%) prepared in Example 1 of this invention at 55°C. Detailed Implementation

[0030] The following specific embodiments further illustrate the technical solution of the present invention. These specific embodiments do not represent a limitation on the scope of protection of the present invention. Non-essential modifications and adjustments made by others based on the concept of the present invention still fall within the scope of protection of the present invention.

[0031] Unless otherwise specified, the experimental methods used in the embodiments of this invention are conventional methods; the materials and reagents used are commercially available unless otherwise specified. Unless otherwise specified, the same parameter value is used in all embodiments.

[0032] The "amorphous composite layer" described in this invention refers to an amorphous interface phase with long-range disorder in its microstructure, formed by the in-situ reaction of lithium fluoride and zirconium fluoride on the surface of nano-silicon powder under specific heat treatment conditions. Specifically, the "amorphous" nature manifests in X-ray powder diffraction (XRD) testing, where it does not exhibit sharp diffraction peaks belonging to the coating component, but only presents a diffuse background scattering signal. This composite layer can effectively suppress side reactions between the silicon-based core and the sulfide electrolyte.

[0033] Example 1 0.95 g of nano-silicon powder (purity > 99.9%), 0.01 g of lithium fluoride (LiF, battery grade), and 0.04 g of zirconium fluoride (ZrF4, 99.99%) were added to a 100 mL zirconium oxide ball mill jar with a ball-to-powder ratio of 20:1. Under the protection of high-purity argon gas, the mixture was ball-milled at a low speed of 300 rpm for 2 h to obtain a uniform premixed powder. The premixed powder was transferred to an alumina boat and placed in a tube furnace for heat treatment under the protection of flowing argon gas (flow rate 200 mL / min). The temperature was increased to 450 °C at a rate of 5 °C / min and held for 3 h to allow zirconium fluoride and lithium fluoride to react in situ on the surface of the nano-silicon powder to form an amorphous composite layer. The mixture was then allowed to cool naturally in the furnace. After cooling, the material is lightly crushed and passed through a 400-mesh sieve to obtain a silicon-based anode active material with an amorphous composite layer. According to the raw material feeding ratio, the mass fraction of the amorphous composite layer in the anode active material is about 5 wt%, so the anode active material is named Si@Li-Zr-F-5.

[0034] Example 2 Compared with Example 1, the only difference is that 0.9g of nano-silicon powder (purity > 99.9%), 0.02g of lithium fluoride (LiF, battery grade), and 0.08g of zirconium fluoride (ZrF4, 99.99%) were added to a 100 mL zirconium oxide ball mill jar at a ball-to-powder ratio of 20:1. High-purity argon gas was introduced for protection, and the milling was performed at 400 rpm for 3 hours to obtain a uniform premixed powder. The heat treatment temperature was 500℃, and the holding time was 2 hours. All other process steps and parameters were exactly the same as in Example 1. In the obtained negative electrode active material, the mass fraction of the amorphous composite layer was approximately 10 wt%, and the negative electrode active material was named Si@Li-Zr-F-10%.

[0035] Example 3 Compared with Example 1, the only difference is that 0.85g of nano-silicon powder (purity > 99.9%), 0.03g of lithium fluoride (LiF, battery grade), and 0.12g of zirconium fluoride (ZrF4, 99.99%) were added to a 100mL zirconium oxide ball mill jar at a ball-to-powder ratio of 20:1. High-purity argon gas was introduced for protection, and the milling was performed at 350rpm for 4 hours to obtain a uniform premixed powder. The heat treatment temperature was 500℃, and the holding time was 2 hours. All other process steps and parameters were exactly the same as in Example 1. In the obtained negative electrode active material, the mass fraction of the amorphous composite layer was approximately 15wt%, and the negative electrode active material was named Si@Li-Zr-F-15%.

[0036] Example 4 Compared with Example 1, the only difference is that 0.8g of nano-silicon powder (purity > 99.9%), 0.04g of lithium fluoride (LiF, battery grade), and 0.16g of zirconium fluoride (ZrF4, 99.99%) were added to a 100mL zirconium oxide ball mill jar at a ball-to-powder ratio of 20:1. High-purity argon gas was introduced for protection, and the milling was performed at 500rpm for 2 hours to obtain a uniform premixed powder. The heat treatment temperature was 500℃, and the holding time was 2 hours. All other process steps and parameters were exactly the same as in Example 1. In the obtained negative electrode active material, the mass fraction of the amorphous composite layer was approximately 20wt%, and the negative electrode active material was named Si@Li-Zr-F-20%.

[0037] Comparative Example 1 Nano-silicon powder (Si with purity > 99.9%) is used as the negative electrode active material.

[0038] Comparative Example 2 Nano-silicon powder (purity > 99.9%), lithium fluoride (LiF, battery grade), and zirconium fluoride (ZrF4, 99.99%) were mixed in the proportions of Example 1, but without undergoing a 450°C heat treatment process to prepare a comparative material, named Si-LZF-Ref composite material. The Si-LZF-Ref composite material was used as the negative electrode active material.

[0039] Performance testing The samples obtained from the above embodiments were tested as follows.

[0040] 1. Characterization of negative electrode active materials 1.1 XRD Test: The negative electrode active materials described in Examples 1-4 and Comparative Example 1 were tested using an X-ray powder diffractometer.

[0041] Test procedure: The test used Cu target Kα radiation (λ=1.5406). The tube voltage is 40 kV, the tube current is 40 mA, the scanning range is 10°–80°, the scanning step size is 0.02°, and the scanning rate is 10° min. -1 After the sample is thoroughly ground in an inert atmosphere, it is placed on the sample stage and the sample surface is flattened as much as possible to obtain a stable and repeatable diffraction signal.

[0042] Results Analysis: The test results are as follows: Figure 1 As shown, the anode active materials (Si@Li-Zr-F-5%, Si@Li-Zr-F-10%, Si@Li-Zr-F-15%, and Si@Li-Zr-F-20%) described in Examples 1-4 only exhibited diffraction peaks at 28°, 47°, and 56°, which correspond one-to-one with the peak positions on the PDF#27-1402 card for Si, indicating that the main phase of the synthesized silicon-based composite material is silicon. Simultaneously, all characteristic peaks of the crystalline LiF and ZrF4 that should have appeared completely disappeared, indicating that this process enables LiF and ZrF4 to fully participate in the in-situ reaction to generate the amorphous Li–Zr–F phase. In contrast, the XRD pattern of the comparative example Si-LZF-Ref still shows diffraction peaks other than silicon, indicating that without a heat treatment process, LiF and ZrF4 cannot be fully converted into the amorphous Li–Zr–F composite phase, thus failing to effectively construct the silicon-based composite anode material.

[0043] 1.2 SEM Testing: The microstructure and surface coating of the material were observed using a scanning electron microscope (SEM).

[0044] Testing Procedure: SEM testing was performed using a field emission scanning electron microscope. Before testing, the obtained powder sample was uniformly fixed on a conductive tape and transferred to the sample chamber under an inert atmosphere or in a dry environment. The accelerating voltage was 5 kV, the working distance was approximately 10.5 mm, and the magnification was 10,000–50,000 times, used to observe the particle morphology of the obtained silicon-based composite anode material.

[0045] Results Analysis: SEM images revealed a uniform and continuous coating layer on the surface of the composite material obtained in the examples. Compared to the materials described in Comparative Examples 1-2, the silicon particles in the examples exhibited a more uniform surface morphology, with the particles being continuously coated, indicating that the LiF-ZrF4 system can achieve sufficient wetting, diffusion, and in-situ recombination on the nano-silicon surface during heat treatment. Further EDS mapping results showed that although the content of F and Zr elements was low, their distribution was relatively uniform, and no obvious elemental segregation or large-sized enrichment regions were observed, indicating that the fluorine and zirconium components were uniformly coated on the silicon particle surface. These results demonstrate that the method of this invention can successfully construct a uniform and continuous amorphous composite layer on the surface of silicon-based particles.

[0046] 2. Assembly and electrochemical testing of all-solid-state half-cells 2.1 Half-cell assembly: All-solid-state half-cells were assembled using the materials described in Examples 1-4 and Comparative Examples 1-2 as negative electrode active materials, respectively. 100 mg of commercial Li 5.5 PS 4.5 Cl 1.5 Electrolyte powder is compressed into sheets.

[0047] Take 7 mg of negative electrode active material (Si, Si-LZF-Ref, Si@Li-Zr-F-5%, Si@Li-Zr-F-10%, Si@Li-Zr-F-15% and Si@Li-Zr-F-20%), 2 mg of commercial Li 5.5 PS 4.5 Cl 1.5 After the electrolyte powder is mixed evenly with 1mg of conductive carbon black, it is spread on one side of the electrolyte sheet and pressed for 3 minutes. Lithium-indium alloy is spread on the other side of the electrolyte sheet, and then the pressure is maintained for 5 minutes to assemble a half cell.

[0048] 2.2 First-cycle coulombic efficiency and discharge specific capacity test: All-solid-state half-cells assembled with the negative electrode active materials (Si@Li-Zr-F-5%, Si@Li-Zr-F-10%, Si@Li-Zr-F-15%, and Si@Li-Zr-F-20%, Si) described in Examples 1-4 and Comparative Example 1 were tested for first-cycle coulombic efficiency and discharge specific capacity.

[0049] Test Procedure: Under constant temperature conditions, constant current charge-discharge tests were conducted using the Xinwei Battery Testing System. The test cutoff voltage range was set to -0.61 to 1.38 V. The test procedure followed the provisions for constant current charge-discharge testing in the relevant national standards for lithium-ion battery electrical performance testing, and was set in accordance with the actual voltage window of the battery system used in this experiment. The first three cycles were conducted at 0.3 A g. -1 The current density was then measured, followed by a test at 0.6 A g. -1 Current density cycling.

[0050] Results Analysis: The test results are as follows: Figure 4 As shown in the figure, battery cycle tests reveal that the amorphous layer composite negative electrode active materials in Examples 1-4 exhibit higher first-cycle coulombic efficiency and discharge specific capacity than pure silicon materials.

[0051] 2.3 Electrochemical impedance spectroscopy (EIS) test: The all-solid-state half-cells assembled from the negative electrode active materials (Si@Li-Zr-F-5%, Si, Si-LZF-Ref) described in Example 1 and Comparative Examples 1-2 were subjected to AC impedance testing.

[0052] Test procedure: Under constant temperature environment, after the battery under test is allowed to stand until the open circuit voltage stabilizes, electrochemical impedance spectroscopy is performed using an electrochemical workstation. The test frequency range is 100 kHz to 0.01 Hz, and the AC disturbance amplitude is 5 mV. The obtained impedance spectrum is used to characterize the internal interface impedance of the battery.

[0053] Results Analysis: The results are as follows Figure 5 As shown, the interfacial impedance of the silicon powder electrode is approximately 227 Ω, the Si-LZF-Ref electrode is approximately 172 Ω, while the Si@Li-Zr-F-5% electrode has an interfacial impedance of only approximately 65 Ω, about one-quarter that of the silicon powder electrode. This result indicates that coating with the amorphous Li-Zr-F fluorine-containing fast ion conductor significantly improves interfacial ion transport between the silicon anode and the sulfide solid electrolyte, resulting in a substantial reduction in interfacial impedance.

[0054] 3. Assembly and electrochemical testing of the full cell 3.1 Full Battery Assembly: The negative electrode active material is the silicon-based composite material (Si@Li-Zr-F-5%) prepared in Example 1, and the electrolyte is commercially available Li. 5.5 PS 4.5 Cl 1.5 Electrolyte powder, positive electrode active material is LiNi 0.9 Co 0.05 Mn 0.05 O2 (NCM9055). NCM9055 and commercial Li... 5.5 PS 4.5 Cl 1.5 Electrolyte powder and conductive carbon fiber were mixed uniformly in a planetary mixer at a mass ratio of 8:1:1 to obtain composite cathode powder. 100 mg of commercial Li was then used. 5.5 PS 4.5 Cl 1.5 Electrolyte powder is pressed into sheets. Take 4 mg of negative electrode active material (Si@Li-Zr-F-5%) and 0.5 mg of commercially available Li... 5.5 PS 4.5 Cl 1.5 After the electrolyte powder and 0.5 mg of conductive carbon black are mixed evenly in a planetary mixer, the mixture is spread on one side of the electrolyte sheet and pressed for 3 minutes. Then, 50 mg of composite cathode powder is evenly spread on the other side of the electrolyte sheet and pressed into a sheet. After pressing for 5 minutes, the sheet is assembled into an all-solid-state battery.

[0055] 3.2 Full-cell electrochemical performance testing: Test procedure: Constant current charge-discharge test was conducted using the Xinwei battery testing system. The test voltage was 2.8~4.3V. The first 3 cycles were performed at 0.1C (1C = 200mAh g). -1 The current density was tested, and then the cycle was continued at a current density of 1C at a test temperature of 55 ℃.

[0056] Results Analysis: The results are as follows Figure 6 As shown, the silicon-based composite material also exhibits good initial coulombic efficiency (75%) and rate performance at 55°C.

[0057] The above results collectively demonstrate that the amorphous Li-Zr-F fast ion conductor prepared in this invention achieves a strong composite bond with silicon, significantly enhancing the lithium-ion conductivity of the silicon-based composite anode active material. Simultaneously, the excellent mechanical properties of the amorphous phase buffer the volume expansion of silicon and form a stable Li-Zr-F-rich protective layer in situ at the anode-electrolyte interface, suppressing harmful side reactions and reducing the interfacial impedance between the anode and the sulfide electrolyte. These multiple synergistic effects enable silicon-based all-solid-state lithium-ion batteries to achieve higher initial coulombic efficiency, lower interfacial impedance, superior rate performance, and cycle stability, fully demonstrating the significant technical advantages of this invention in solving the key bottleneck problem of silicon anodes in sulfide all-solid-state batteries.

Claims

1. A negative electrode active material, characterized in that, include: A silicon-based core, and an amorphous composite layer in situ coated on the surface of the silicon-based core; In the XRD pattern of the negative electrode active material, only the characteristic diffraction peaks of elemental silicon appear, and the crystalline characteristic peaks of the raw material corresponding to the amorphous composite layer do not appear.

2. The negative electrode active material according to claim 1, wherein the average particle size D50 of the silicon-based core is 50 nm to 5 μm.

3. The negative electrode active material according to claim 1, characterized in that, The amorphous composite layer has a mass fraction of 2wt% to 30wt% in the negative electrode active material.

4. The negative electrode active material according to claim 1, characterized in that, The amorphous composite layer is generated by an in-situ reaction of lithium fluoride, zirconium fluoride and the silicon-based core.

5. The negative electrode active material according to claim 1, characterized in that, The amorphous composite layer contains Li, Zr and F elements, and the molar ratio of Li, Zr and F satisfies: Li:Zr:F = (0.5~3) : (0.2~1) : (3~8).

6. The negative electrode active material according to claim 1, characterized in that, The negative electrode active material satisfies the following parameter characteristics: The characteristic diffraction peaks of the elemental silicon are located at 2θ of 28°±0.5°, 47°±0.5°, and 56°±0.5°.

7. A method for preparing a negative electrode active material as described in any one of claims 1-6, characterized in that, Includes the following steps: S1. Nano-silicon powder, lithium fluoride and zirconium fluoride are mixed to obtain a premixed powder; S2. The premixed powder is heat-treated to cause lithium fluoride and zirconium fluoride to react in situ on the surface of nano-silicon powder to generate the amorphous composite layer.

8. The preparation method according to claim 7, characterized in that, The method satisfies at least one of the following parameter characteristics: (a) The mixing process includes a mechanical grinding process, wherein the mechanical grinding process is selected from at least one of ball milling, sand milling, planetary milling, and roller milling; (b) The ball-to-material ratio of the mixed treatment is (15~25):1; (c) The rotation speed of the mixing process is 50~500 rpm; (d) The mixing process takes 0.5 to 6 hours; (e) The heat treatment is carried out in an inert atmosphere selected from at least one of helium, neon, argon and nitrogen; (f) The heat treatment temperature is 400°C to 900°C; (g) The heat treatment holding time is 0.5~4h.

9. The preparation method according to claim 7, characterized in that, After the heat treatment described in step S2, the process further includes: rapidly cooling, grinding, and sieving the heat-treated product; The rapid cooling condition is as follows: the product temperature is reduced to room temperature within 5-10 minutes; The preferred mesh size for sieving is 400 mesh or higher.

10. The application of the negative electrode active material according to any one of claims 1-6 in an all-solid-state battery.

11. A secondary battery, characterized in that, Includes the negative electrode active material as described in any one of claims 1-6.

12. The secondary battery according to claim 11, characterized in that, The secondary battery is a lithium-ion battery.